”En ny hverdag”. Mødres opplevelse av hverdagen med et prematurt barn, og støtten ved en ressurshelsestasjon - Sørby, Solveig; Fegran, Liv (Nordisk tidsskrift for helseforskning, 2015)
The study explores mothers’ of premature infants experience of how health centers especially adapted for families with premature infants can help them to cope with everyday life after discharge from a neonatal intensive care unit. Background: Premature children are at higher risk for physical and mental health problems, which makes parenting demanding. The transition between hospital and home is a challenging period where parents may need extra support to cope with everyday life. Method: Nine mothers of premature infants receiving follow-up care at a health center especially adapted for families with premature infants were interviewed. Data were analyzed by Kvale and Brinkmann’s guidelines for text analysis. Findings: The study revealed that mothers of premature infants need to adapt to a daily life with both challenges and joys. Mothers’ sense of coping in everyday life is affected by the public health nurse’s knowledge of and experience with premature infants. Conclusion: Mothers of premature infants experience a challenging daily life after discharge from neonatal intensive care unit. A health center especially adapted for families with premature infants can help mothers cope with everyday life after discharge through availability, flexibility, expertise, facilitating a social network and focusing on mothers’ own experience of their daily life.